SUBJECT: DEVELOPING STUDENTS' INDEPENDENCE IN ACQUIRING KNOWLEDGE AS A PEDAGOGICAL PROBLEM (International journal of artificial intelligence, 2024)
Self-activation is considered one of the most important principles of learning. It is the basis for the development of human consciousness, will, memory, thinking and other qualities. “What a person does not possess as an amateur performance is not his”